Study of The Caregivers Role Strain in Fulfilling Nutrition for Stunting Toddlers In Public Health Center of Rambipuji, Jember regency: Studi Ketegangan Peran Pemberi Asuhan dalam Pemenuhan Nutrisi Balita Stunting di Wilayah Kerja Puskesmas Rambipuji Kabupaten Jember - Riski Hidayaturrohkim; Tantut Susanto; Hanny Rasni; Syahroni Bahtiar (Caring : Jurnal Keperawatan, 2022)
Stunting in toddlers gets serious attention because it affects motor development delays and decreased intelligence while the family has an essential function and role in fulfilling nutritional needs. This study aims to describe family nursing care to overcome the caregivers role strain in fulfilling stunting toddler nutrition. This research method uses a case study with a 3-week approach to family nursing care. The participants involved were two families assisted by stunting toddlers in the Public Health Center of Rambipuji. Data were collected through interviews, observation, and physical examination. After conducting a family assessment, it was found that the problem of the caregivers role strain was found. Then nursing interventions were given including education for caregivers, child nutrition education, and nutrition management showing increased knowledge about stunting, children's nutritional needs, my plate diet method, and making additional food for toddlers and families being able to provide food according to toddler needs. There is an increase in body weight in Mr.M family toddlers by 0.5 kg, and Mr.A family toddlers by 0.6 kg with an increase in their height of 1 cm. Increased family knowledge affects behavior and improves health conditions in fulfilling the nutritional needs of toddlers which encourage the achievement of optimal family independence.   Stunting pada balita mendapatkan perhatian serius karena berdampak keterlambatan perkembangan motorik dan penurunan intelegensia sementara keluarga mempunyai fungsi dan peran esensial dalam pemenuhan kebutuhan nutrisi. Penelitian ini bertujuan untuk mendiskripsikan asuhan keperawatan keluarga untuk mengatasi ketegangan peran pemberi asuhan dalam pemenuhan nutrisi balita stunting. Metode penelitian ini menggunakan studi kasus dengan pendekatan asuhan keperawatan keluarga selam 3 minggu. Partisipan yang terlibat sebanyak dua keluarga binaan balita stunting di wilayah Puskesmas Rambipuji. Pengambilan data dilakukan melalui wawancara, observasi dan pemeriksaan fisik. Setelah dilakukan pengkajian keluarga didapatkan masalah ketegangan peran pemberi asuhan. Kemudian  diberikan intervensi keperawatan  meliputi edukasi pada pengasuh, edukasi nutrisi anak dan manajemen nutrisi menunjukkan peningkatkan pengetahuan tentang stunting, kebutuhan nutrsi anak, metode diet isi piringku, dan pembuatan makanan tambahan balita serta keluarga mampu menyediakan makanan sesuai kebutuhan balita. Terdapat peningkatan berat badan pada balita keluarga Tn. M sebesar 0,5 kg, dan  balita keluarga Tn. A sebesar 0,6 kg dengan penambahan tinggi badan keduanya 1 cm. Peningkatan pengetahuan keluarga mempengaruhi perilaku dan memperbaiki kondisi kesehatan dalam memenuhi kebutuhan nutrisi balita yang mendorong pencapaian kemandirian keluarga scara optimal.